2023
DOI: 10.1172/jci.insight.150368
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic TET2 mutations confer sensitivity to 5′-azacitidine in acute myeloid leukemia

Abstract: Precision medicine can significantly improve outcomes for cancer patients, but implementation requires comprehensive characterization of tumor cells to identify therapeutically exploitable vulnerabilities. Here we describe somatic biallelic TET2 mutations in an elderly patient with acute myeloid leukemia (AML) that was chemoresistant to anthracycline and cytarabine (Ara-C), but acutely sensitive to 5'-azacitidine (5'-Aza) hypomethylating monotherapy resulting in longterm morphological remission. Given the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…However, mutations result in reduced levels of functional TET2 whereas silencing by promoter methylation, as seen in T-ALL, causes a complete loss of the protein and can therefore have different consequences. A recent study, for example, showed that only a complete loss of TET2 in the form of bi-allelic lossof-function mutations sensitised AML patients to AZA [410].…”
Section: Cytotoxicity In Response To Hypomethylating Agents Is Associ...mentioning
confidence: 99%
“…However, mutations result in reduced levels of functional TET2 whereas silencing by promoter methylation, as seen in T-ALL, causes a complete loss of the protein and can therefore have different consequences. A recent study, for example, showed that only a complete loss of TET2 in the form of bi-allelic lossof-function mutations sensitised AML patients to AZA [410].…”
Section: Cytotoxicity In Response To Hypomethylating Agents Is Associ...mentioning
confidence: 99%
“…These variants presented overexpression of the multidrug efflux pump P-glycoprotein (P-gp) and exhibited resistance to P-gp relative substances in addition to resistance to AZA [10]. Similarly, AZA-resistant variants of HEL cells (a cell line of leukemic erythroblasts) showed increased levels of P-gp expression [11]. Such cells exhibit a multidrug resistance of the P-glycoprotein type and may not have activated specific mechanisms typical for the development of resistance to demethylating agents.…”
Section: Introductionmentioning
confidence: 99%